A methods engineering study of Progressive Laboratories, Inc. - Falcis, Charlene Therese; Herrin, Mark Andrew; Varona, Andrew James (Department of Industrial Engineering and Operations Research College of Engineering, University of the Philippines Diliman, Quezon City, 2000)
Progressive Laboratories is a veterinary and pharmaceutical testing laboratory that has expanded into contact toll manufacturing and contact packaging over the years. Its wide range of products includes premixes, powders, vitamins and antibiotics. The product in study is Vermigo, an anthelmintic or a dewormer in tablet form, which is the largest product line of the company's biggest client, Univet. It has an elliptical shape and is colored in industrial blue. Ten of the tablets are packed in one blister, and ten blisters are packed in one family box. In the course of the study, it has been observed that there are a lot of delays in the production, and that much of the delay stems from the undue length of the packaging operation. The 3-day packaging operation takes twice or even thrice as long as the other operations in the Vermigo production. Its three elements, the sorting process, the manual packing process and the blister packing process are studied and it is found out that the first two, which are manually done actually take the longest to finish. The workers are not fully utilized, and this is due to the cramped layout of the packaging room and the inefficiency of the sorting and packing methods. To shorten the entire packaging process of Vermigo, alternatives are generated. These are : the establishment of two sets of a 2 workstation assembly line, improvement of the sorting process and rearrangement of the packaging room layout. With these alternatives, the workers will be more productive and will be able to work more comfortably. Team effort, instead of individual ones, will be the focus. The decrease of the length of the packaging operation will decrease the overall length of Vermigo production, therefore increasing Progressive Laboratories' productivity and improving its efficiency.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Progressive Laboratories; Pharmaceutical industry; Systems analysis